Adenylate Cyclase Mutations Rescue the degP Temperature-Sensitive Phenotype and Induce the Sigma E and Cpx Extracytoplasmic Stress Regulons in Escherichia coli - Strozen, Timothy G. (American Society for Microbiology, 2005)
Inactivation of the gene encoding the periplasmic protease DegP confers a high-temperature-sensitive phenotype in Escherichia coli. We have previously demonstrated that a degP mutant of E. coli strain CBM (W3110 pldA1) is not temperature sensitive and showed that this was most likely due to constitutive activation of the sigma E and Cpx extracytoplasmic stress regulons in the parent strain. In this study, further characterization of this strain revealed a previously unknown cryptic mutation that rescued the degP temperature-sensitive phenotype by inducing the extracytoplasmic stress regulons. We identified the cryptic mutation as an 11-bp deletion of nucleotides 1884 to 1894 of the adenylate cyclase-encoding cyaA gene (cyaAΔ11). The mechanism in which cyaAΔ11 induces the sigma E and Cpx regulons involves decreased activity of the mutant adenylate cyclase. Addition of exogenous cyclic AMP (cAMP) to the growth medium of a cyaAΔ11 mutant strain that contains a Cpx- and sigma E-inducible degP-lacZ reporter fusion decreased β-galactosidase expression to levels observed in a cyaA(+) strain. We also found that a cyaA null mutant displayed even higher levels of extracytoplasmic stress regulon activation compared to a cyaAΔ11 mutant. Thus, we conclude that the lowered concentration of cAMP in cyaA mutants induces both sigma E and Cpx extracytoplasmic stress regulons and thereby rescues the degP temperature-sensitive phenotype.